Interrogando o livro: a arte responde - Pereira, Rômulo do Nascimento (2014)
This search has as its object the book, its history, formal and symbolic features, and especially your conscious use for the construction of an artistic work. This appropriation and the study made of it part of the graphic look, materiality that makes the book being what it is, and go beyond. Search discern in many pages, folds, stories, characters, the concepts and contacts with art that the book is more than an interface between text and reader. A place for invention and revolution that affect both, making it, often an almost human object, perhaps an extension. To accompany it backs-up to thousands of years when he turned a stone after papyrus, and design you will be in a few decades. We follow his path to the side of art for centuries and different characters, the early 20th century to reach the 1960, period in which this gentleman, in Brazil, starts to be used by artists and converted into proposition. Arts and editing are called to collaborate and their frequent contacts are observed until you have one: artist book. Disturbing production and contemporary art, and always difficult to define, they are extending paths, inventing help them to reinvent the book. Did not prevent such a task, place some limits, to be able to understand what they tell us, and how. Knowledge was put to the test in carrying in productions, hybrid objects, having the error in the printed book as a theme, as the start of a particular writing. Keywords: history of book, graphic arts, artist’s books, visual arts, creating